Hubungan antara Efikasi Diri dengan Burnout pada Petani Karet Di PTPN XII Kebun Renteng Jember - Ardhia Christie Femila Surya; Erti Ikhtirini Dewi; Enggal Hadi Kurniawan (Pustaka Kesehatan, 2023)
Rubber farmers are one of the professional which is risk of experiencing burnout. The routine of work by rubber farmers which is repeatedly over a long period of time, namely planting, maintenance and tapping can lead to burnout. One of the factors that influence an individual to resist burnout is self-efficacy. This study aims to analyze the relationship between self-efficacy with burnout in rubber farmers at PTPN XII Kebun Renteng Jember Regency. Design of this study were an quantitative correlational with cross-sectional approach. The population was 523 respondents. A total of 227 respondents were obtained by simple random sampling. Randomization of responden by research randomizer. The data collection used the General Self Efficacy (GSE) questionnaire and the Maslach Burnout Inventory-General Survey (MBI-GS). The data analysis used the Spearman test with a significance level of 0.05. The results showed that the median value of self-efficacy was 35, while the mean value of burnout was 40,09. There was a relationship between self-efficacy with burnout in rubber farmers at PTPN XII Kebun Renteng Jember Regency (p-value = 0,001; r = -0,216). The determinant coefficient (r) of 0.216 indicated that the level of correlation is low.